Orthognatıc Surgery In Class Iıı Cases (Case Report) - Orhan Güven (Galenos Yayinevi, 1988)
If the maximum potential of surgical-orthodontic treatment is to be realised, treatment planning must include consideration of facial as well as dental relationships. It is no longer enough to manuplate dental casts only in planning surgical procedures on the jaws. Six major relationships must be evaluated in planning treatment for dentofacial problems: maxilla to cranium, mandible to cranium, maxilla to mandible, and maxillary teeth to maxilla, mandibular teeth to mandible, and maxillary teeth to mandibular teeth. Of these only the last can be seen on dental casts. Cephalometric analysis and orthognatic model surgery are necessary to evaluate other relationships. In this paper correction of mandibular prognathism operated without being planned previously has been presented.